Point-count bird censusing: long-term monitoring of bird abundance and diversity along the Salt River in the greater Phoenix metropolitan area, ongoing since 2013 (Reformatted to the ecocomDP Design Pattern) - Heather Bateman; Paige Warren (Environmental Data Initiative, 2021)
This data package is formatted as an ecocomDP (Ecological Community Data Pattern). For more information on ecocomDP see https://github.com/EDIorg/ecocomDP. This Level 1 data package was derived from the Level 0 data package found here: https://pasta.lternet.edu/package/metadata/eml/knb-lter-cap/641/6. The abstract below was extracted from the Level 0 data package and is included for context: